Teachers as Reflective Practitioners: From Individualism to Vygotskian Social Constructivism - Shah, Muhammad Athar (Alberta Journal of Educational Research, 2022)
The paper presents a critical review of major works on reflective practice in teaching that mainly define reflection as a technical and isolated process, taking place in an individual’s mind. Critiquing the cognitive nature of reflective practice promoted in mainstream research, the paper directs attention to the increasing recognition of sociocultural factors in teacher professional learning, and highlights the significance of reflection as a social practice. Starting with the ideas of John Dewey on reflective practice for teachers, the paper delineates Schön’s successive works on the subject, followed by a discussion of Wallace’s reflective model. The final part of the paper describes how Vygotsky’s sociocultural theory provides a theoretical framework for teachers to effectively engage in reflective practice by moving from individualism to social constructivism in their efforts to enhance their professional competence. Keywords: reflection; reflective practitioner; teacher professional learning; Vygotsky; social constructivism L'article présente un examen critique des principaux travaux sur la pratique réflexive dans l'enseignement qui définissent principalement la réflexion comme un processus technique et isolé, se déroulant dans l'esprit d'un individu. Critiquant la nature cognitive de la pratique réflexive promue par la recherche dominante, l'article attire l'attention sur la reconnaissance croissante des facteurs socioculturels dans l'apprentissage professionnel des enseignants et souligne l'importance de la réflexion en tant que pratique sociale. Partant des idées de John Dewey sur la pratique réflexive pour les enseignants, l'article décrit les travaux successifs de Schön sur le sujet, pour ensuite discuter du modèle réflexif de Wallace. La dernière partie de l'article décrit la mesure dans laquelle la théorie socioculturelle de Vygotsky fournit un cadre théorique permettant aux enseignants de s'engager efficacement dans une pratique réflexive en passant de l'individualisme au constructivisme social dans leurs efforts pour améliorer leur compétence professionnelle. Mots clés : réflexion ; praticien réfléchi ; apprentissage professionnel des enseignants ; Vygotsky ; constructivisme social